The Hsp70-Hsp90 co-chaperone Hop/Stip1 shifts the proteostatic balance from folding towards degradation - Kaushik Bhattacharya; Lorenz Weidenauer; Tania Morán Luengo; Ellis C. Pieters; Pablo C. Echeverría; Lilia Bernasconi; Diana Wider; Yashar Sadian; Margreet B. Koopman; Matthieu Villemin; Christoph Bauer; Stefan G. D. Rüdiger; et al. (Nature Communications, 2020)
Hop, also known as Stip1 or Sti1, facilitates substrate transfer between the Hsp70 and Hsp90 molecular chaperones. Characterization of proteostasis-related pathways in STIP1 knock-out cell lines reveals that in eukaryotes Stip1 modulates the balance between protein folding and degradation.